A combined study of genetic association and brain imaging on the DAOA gene in schizophrenia12. Issue 2 (17th January 2013) - Chen, Jun; Xu, Yong; Zhang, Juan; Liu, Zhifen; Xu, Cheng; Zhang, Kerang; Shen, Yan; Xu, Qi
Abstract While there has been no objective biomarker available for both diagnosis and prognosis of schizophrenia, compelling evidence suggests that the glutamatergic system may influence susceptibility to schizophrenia. To test genetic association of the glutamatergic system with schizophrenia and abnormal brain activities in resting‐state patients with schizophrenia, a two‐stage association study was performed in 454 patients and 480 controls, followed by regional homogeneity (ReHo) analysis of resting‐state functional magnetic resonance imaging in 48 first‐episode medication‐free patients and 43 well‐matched controls. The differences in ReHo between genotypes of interest were initially tested by the Student's t‐test and the 2 × 2 (genotypes × disease status) ANOVA was then performed to identify the main effects of genotypes, disease status and their interactions in schizophrenia. The stage‐1 study showed association of the DAOA and PSEN2 genes with schizophrenia in a small sample; the stage‐2 study with an expanded sample confirmed the disease association for 2‐SNP and 3‐SNP haplotypes, and the cis‐phase interactions between rs2391191 and some other SNPs in the DAOA gene. Four clusters with altered ReHo in the bilateral culmen, left putamen and left cuneus were associated with rs2391191. Main effects of rs2391191 genotypes were found in the left putamen. The left cuneus showed a genotype × disease status interaction. In conclusion, the DAOA gene may confer genetic risk of schizophrenia and associate with the altered ReHo in schizophrenia; genotype effect and its interaction with disease status may contribute to the altered ReHo, leading to specific ReHo in schizophrenic brain due to glutamatergic modulation. © 2013 Wiley Periodicals, Inc.